Trade, value chains, and rent distribution with foreign exchange controls: Coffee exports in Ethiopia - Tamru, Seneshaw; Minten, Bart; Swinnen, Johan (Agricultural and Applied Economics Association, 2021)
Exchange rate policies can have important implications on incentives for export agriculture. However, their effects are often not well understood. We study the issue of foreign exchange controls and pricing in the value chain for Ethiopia's coffee—its most important export crop. Relying on unique pricing and cost data, we find that coffee exporters are willing to incur losses during exporting by offering high prices for coffee locally in order to access scarce foreign exchange. We further find that the consequent high wholesale prices for coffee are transmitted to producers, so that coffee farmers are unintended beneficiaries of this rent.